Driving SME internationalization through digital transformation strategies - Muchamad Rizky Fauzi; Sudarmiatin Sudarmiatin; Heri Pratikto (PT Aksara Indo Rajawali, 2026)
Purpose – This study aims to systematically identify, evaluate, and synthesize the existing empirical evidence on digital platform strategies adopted by small and medium-sized enterprises (SMEs) for internationalization, to map the types of platforms used, the strategic approaches employed, the factors mediating and moderating their effectiveness, and the emerging trends reshaping the digital internationalization landscape. Design/methodology/approach – A Systematic Literature Review (SLR) was conducted in accordance with the PRISMA 2020 protocol. A keyword-based search of the Scopus database retrieved peer-reviewed, open-access, English-language articles in their final publication stage, published between 2015 and 2025. Fifty-nine articles met all inclusion criteria and were subjected to thematic analysis following the six-phase framework of Braun and Clarke (2006). The theoretical foundation draws on the Resource-Based View (RBV), dynamic capabilities theory, institutional theory, and the Technology-Organization-Environment (TOE) framework. Findings – Five themes were identified. First, social platforms consistently outperform commercial platforms in driving internationalization outcomes; hybrid strategies that combine owned digital assets with selective third-party platform engagement are the most effective approach. Second, business model innovation (BMI) mediates the platform-performance relationship, functioning as an absorptive pathway that converts platform capabilities into sustained international performance gains. Third, managerial digital competencies and organizational culture are foundational prerequisites for successful digital internationalization. Fourth, regional infrastructure, institutional environment, and sector type significantly moderate platform effectiveness, with platforms serving a compensatory role in weak institutional contexts. Fifth, AI, blockchain, and FinTech extend SME platform capabilities considerably but face significant barriers to adoption. Research limitations – The review is limited to a single database (Scopus), English-language publications, and open-access articles in the final publication stage, which may have excluded relevant studies. The predominance of manufacturing- and technology-intensive SME contexts in the reviewed literature limits the generalizability to service-oriented and informal-economy SMEs. Future research should prioritize longitudinal studies; adaptive digital maturity models that integrate ecosystem dynamics; mixed-methods investigations of platform trust-building mechanisms in weak institutional environments; and SME-specific Industry 4.0 implementation frameworks. Implications – For SME practitioners, the findings recommend prioritizing investment in social platforms, pairing platform adoption with deliberate business model reconfiguration, and adopting hybrid digital strategies. For policymakers, developing an integrated digital ecosystem that addresses connectivity infrastructure, digital literacy, and gender equity is essential. Platform providers should co-design SME-friendly solutions that address skill, financial, and integration barriers. Theoretically, the study advances dynamic capabilities and institutional theories by repositioning BMI as an absorptive pathway and documenting the dual compensatory-efficiency role of platforms across institutional contexts. Originality – This review is among the first to systematically synthesize the multi-dimensional literature on digital platform strategies and SME internationalization across commercial, social, hybrid, and emerging platform types within a single integrative framework. It contributes new theoretical insights by positioning BMI as an absorptive pathway, establishing the superiority of social over commercial platforms, and documenting environmental dynamism as a boundary condition on intellectual capital conversion. It further advances understanding of how platforms compensate for institutional voids in developing and emerging market contexts.